Effectiveness of role play in enhancing the speaking skills of the learners in a large classroom: An investigation of tertiary level students - Islam, Priscilla; Islam, Tazria (Stamford Journal of English, 2013)
This investigation looks at enhancement in learners speaking skills through role play in groups in a large classroom and this study also examines the teachers assessment of students for further development of their speaking skills. About one-hundred twenty students of the department of English, Stamford University Bangladesh were involved in this investigation process from January 2012 until April 2012 in the speaking classes. For the research, qualitative data were collected in the form of questionnaires, group interviews, classroom observation, and students performance evaluation result. The result from class room observations of students performance has been presented in the form of graphic analysis. The result shows learners improvement in speaking skills through role play and how the positive attitudes of teachers help to further their speaking skills. From the response of the students questionnaire it has become obvious that role play has been enthusiastically accepted by the students as it challenges their creativity and ability to think critically, which enables them to speak more logically and confidently in the classroom. The result of the group interview shows the advantages and disadvantages of students performance while doing the role play in groups inside the classroom and it also helps students to overcome inhibition when it comes to speaking in front of others. Through classroom observation the teacher identifies students ability to adapt with the situational factors and also measures their fluency and use of accurate language by recording their performances. The teacher also records the gradual progress of students for further development of their speaking skills and ascertains how beneficial it is to do role play in a large classroom. DOI: http://dx.doi.org/10.3329/sje.v7i0.14475 Stamford Journal of English; Volume 7; Page 218-233